2015
DOI: 10.1111/zph.12229
|View full text |Cite
|
Sign up to set email alerts
|

Human Brucellosis Trends: Re‐emergence and Prospects for Control Using a One Health Approach in Azerbaijan (1983–2009)

Abstract: Brucellosis is one of the most common and widely spread zoonotic diseases in the world. Control of the disease in humans is dependent upon limiting the infection in animals through surveillance and vaccination. Given the dramatic economic and political changes that have taken place in the former Soviet Union, which have limited control, evaluating the status of human brucellosis in former Soviet states is crucial. We assessed annual spatial and temporal trends in the epidemiology of human brucellosis in Azerba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…For instance, changes in the livestock system including an increase in livestock handlers per animal and increasing livestock density in Kazakhstan after the collapse of the USSR have been attributed to brucellosis epidemics (Beauvais, Coker, Nurtazina, & Guitian, 2017). A 2015 analysis of livestock surveillance data in Azerbaijan spanning the transition from Soviet dissolution to independence found that in areas where agriculture production had increased, so did the number of reported human cases of brucellosis (Kracalik et al, 2016). Policies to intensify livestock production have been attributed as one of the key factors in the re-emergence of brucellosis throughout sub-Saharan Africa (Ducrotoy et al, 2014).…”
Section: Regionmentioning
confidence: 99%
“…For instance, changes in the livestock system including an increase in livestock handlers per animal and increasing livestock density in Kazakhstan after the collapse of the USSR have been attributed to brucellosis epidemics (Beauvais, Coker, Nurtazina, & Guitian, 2017). A 2015 analysis of livestock surveillance data in Azerbaijan spanning the transition from Soviet dissolution to independence found that in areas where agriculture production had increased, so did the number of reported human cases of brucellosis (Kracalik et al, 2016). Policies to intensify livestock production have been attributed as one of the key factors in the re-emergence of brucellosis throughout sub-Saharan Africa (Ducrotoy et al, 2014).…”
Section: Regionmentioning
confidence: 99%
“…In view of the low infective dose of B. melitensis , estimated at 10 - 100 colony-forming units [ 12 , 13 , 31 , 32 ], their potential for aerosol dissemination [ 31 ] and the ability of the organisms to cause protracted and incapacitating disease of enormous public health and economic consequences [ 12 , 14 ]; there is need for a coordinated brucellosis prevention and control programs in the study area to limit the spread of Brucella infection. Such programs must include awareness creation on the mode of acquisition or spread of Brucella infection, as well as the public health and economic consequences associated with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the table also indicate that the contents of the material delivered in the program were up-to-date and very relevant to the current situation in the veterinary field. Indeed, the case studies that were used in this PBL-OH program were designed to cater the present climate in zoonotic diseases [ 25 - 28 ]. This information helped the participants to relate the knowledge they learned in the classroom into the actual field scenarios.…”
Section: Discussionmentioning
confidence: 99%